Reticulate reef patterns – antecedent karst versus self‐organization. Issue 2 (27th November 2014) - Schlager, Wolfgang; Purkis, Sam
Abstract: Reticulate ridges of reefs and sediment in Holocene lagoons are usually interpreted as an inheritance of antecedent karst topography. Satellite imagery served as a template for integrating plan‐view geometry with published data from coring, drilling and seismic surveys to test the antecedent‐karst hypothesis. The link between karst morphology and overlying reef patterns can be demonstrated convincingly for a rather limited number of examples, particularly those on a substrate of tower karst with high relief. On very young limestones, doline karst with reticulate patterns develops very slowly because of the high porosity. Moreover, karst control can be ruled out for the significant number of reticulate reefs that are founded on terrigenous sediment or on demonstrably flat pre‐Holocene rock surfaces. One likely cause of reticulate patterns is biotic self‐organization that has been shown to generate reticulate and labyrinthic patterns of mussel beds on tidal flats and tree cover of arid ecosystems. Another pathway to reticulate reefs may be the colonization of reticulate hydrodynamic bedforms by reef builders. Thus, reticulate patterns of Holocene reef‐sediment ridges are highly ambiguous indicators of antecedent karst.